1996
DOI: 10.1097/00004647-199607000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Intracerebral Microdialysis and Positron Emission Tomography in the Detection of Ischemia in Patients with Subarachnoid Hemorrhage

Abstract: Intracerebral microdialysis (MD) was applied in patients with subarachnoid hemorrhage. The regional CBF, the CMRO2, and oxygen extraction ratio (OER) were measured with simultaneous positron emission tomography (PET). The aim was to directly correlate alterations in dialysate levels of energy-related metabolites (lactate, lactate/pyruvate ratio, hypoxanthine) and excitatory amino acids (EAAs) (glutamate and aspartate) to the energy state in the MD probe region as determined by PET. Regional ischemia was define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
1
8

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(113 citation statements)
references
References 19 publications
6
98
1
8
Order By: Relevance
“…Thus, it is possible that seizures resulted in worsening brain edema and hence elevation in ICP. (2,14,17). We have demonstrated that LPR is elevated for 1 wk in previous studies (18).…”
Section: Potential Role Of Electrographic Seizures On Brain Swelling mentioning
confidence: 53%
See 2 more Smart Citations
“…Thus, it is possible that seizures resulted in worsening brain edema and hence elevation in ICP. (2,14,17). We have demonstrated that LPR is elevated for 1 wk in previous studies (18).…”
Section: Potential Role Of Electrographic Seizures On Brain Swelling mentioning
confidence: 53%
“…LPR is thought to represent alterations of mitochondrial function and redox state of the cell (16). LPR can increase with brain ischemia, under conditions of severely limited cerebral blood flow (2,14,17). We have demonstrated that LPR is elevated for 1 wk in previous studies (18).…”
Section: Seizures Are Associated With Prolonged Metabolic Distressmentioning
confidence: 70%
See 1 more Smart Citation
“…However, there is no evidence that 1 method is more efficient and reliable than other methods. [37][38][39] Cumulative meta-analysis, including 1981 patients altogether, demonstrated that the frequency of shunt-dependent hydrocephalus was not significantly different between coiling and clipping. This result differs with the prior meta-analysis conducted in 2007, 40 which showed that the risk of shuntdependent hydrocephalus was significantly higher after coiling than clipping for ruptured intracranial aneurysms.…”
Section: Secondary Outcomesmentioning
confidence: 98%
“…13,14 An increase in lactate to pyruvate (L/P) ratio is a sensitive indicator of brain ischemia, and increases in L/P ratio have been observed after subarachnoid hemorrhage. 15,16 Brain edema of cellular nature is frequently observed, which results in an increase of intracranial pressure (ICP) for more than 5 days. 17 Increased ICP causes structural damage and herniation and reduces cerebral perfusion pressure and cerebral blood flow, leading to further exacerbation of ischemia.…”
Section: Pathophysiology Of Traumatic Brain Injurymentioning
confidence: 99%